Shear behaviour of reinforced palm kernel shell concrete beams - Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Mahmud, H.; Fayyadh, M.M. (Elsevier, 2011)
The shear behaviour of palm kernel shell concrete (PKSC) beams prepared using palm kernel shell (PKS) as lightweight aggregate (LWA) is reported here. The shear strength of grade 30 PKSC with a density of 1850 kg/m3 was found 24 higher than the corresponding normal weight concrete (NWC). Good aggregate interlock in PKSC was evident as it produced shorter jagged cracks compared to longer plain cracks of NWC. Further, PKSC was able to produce twice as many flexural and shear cracks compared to NWC. Tension stiffening between the tensile cracks of PKSC enhanced flexural rigidity and dowel action. The non-linear numerical analysis predicted the shear strength within an average 20 of the experimental results. Â© 2011 Elsevier Ltd. All rights reserved.